2209. Discordance Between FibroSure and FibroScan Results in Hepatitis C and Human Immunodeficiency Virus Co-infected Patients Prior to Treatment for Hepatitis C Virus Infection. (26th November 2018) - Tiyouh, Melissa; Lee, Dong Heun; Franks, Taneesa; Scott, Tiffany; Kesaris, Anna; Chou, Edgar; Coppock, Dagan
Abstract: Background: The accurate diagnosis of hepatitis C virus (HCV)-related fibrosis is crucial for prognosis and treatment decisions. FibroSure and FibroScan are commonly used to approximate fibrosis prior to HCV treatment. Both methods have been validated for their correlation to the five-level (F0–F4) METAVIR scoring system. However, the correlation between these two tests in HIV/HCV co-infected patients has not been well described. Here, we evaluated the concordance between FibroSure and FibroScan-derived METAVIR results in HIV/HCV co-infected patients. Methods: We performed a retrospective cross-sectional study of HIV/HCV co-infected patients that were treated between 2014 and 2017 at Drexel University, Philadelphia, PA. We described patient demographics and overall METAVIR scores of treated patients. Further, we compared the concordance between FibroSure and FibroScan results among patients who had both tests before the start of HCV treatment. Results: One hundred and thirty-eight HIV/HCV co-infected patients were treated. Most of them ( N = 134, 97%) achieved sustained virologic response after 12 weeks of treatment. One hudred and thirty-three patients underwent FibroSure testing before starting HCV treatment. Of those, 62 (47%) fell in the F0–F2 range and 71 (53%) in the F3–F4 range. Of those 133 patients, 21 also underwent FibroScan. Fourteen (67%) fell in the F0–F2 range, while seven (33%) fell in the F3–F4 range. Of the 21 patients who both had FibroSure and FibroScan testing, 12 (57%) had concordant results, while nine (42%) had discrepant results. Of the patients with discrepant results, eight had higher fibrosis scores (F3–F4) with FibroSure, while only one had a higher fibrosis score (F3–F4) with FibroScan. Conclusion: In our study, more than half of HIV/HCV co-infected patients had advanced fibrosis score at the time of HCV treatment. When FibroSure and FibroScan scores were compared, close to half of co-infected patients had discordant results, the preponderance of which had higher FibroSure scores. As early initiation of HCV treatment is crucial to co-infected patients, further studies will need to evaluate the clinical significance of the discrepancy between different non-invasive fibrosis testing systems in co-infected patients. Disclosures: All authors: No reported disclosures.